2010
DOI: 10.1038/ki.2010.69
|View full text |Cite
|
Sign up to set email alerts
|

Paricalcitol attenuates cyclosporine-induced kidney injury in rats

Abstract: Despite its benefits, the clinical use of cyclosporine A (CsA) is limited by its nephrotoxic properties. Because paricalcitol (19-nor-1,25-hydroxyvitamin D(2)) has renoprotective effects, we tested whether it can blunt renal dysfunction and fibrosis in a rat model of CsA-induced nephropathy. Treatment with CsA decreased creatinine clearance, increased monocyte/macrophage infiltration, and increased the expression of inflammatory cytokines within the kidney. Paricalcitol reduced the decline in kidney function a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 33 publications
4
76
0
5
Order By: Relevance
“…Of note, paricalcitol has been shown to improve cardiac oxidative injury in uremic and aortic oxidative injury in atherosclerotic rats [9,23]. Paricalcitol has been shown to attenuate ciclosporin Ainduced nephropathy by suppression of inflammatory and apoptotic factors through inhibition of some protein kinase-signalling pathways [5]. De Zeeuw et al [24] demonstrated that paricalcitol lowers albuminuria in patients with diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, paricalcitol has been shown to improve cardiac oxidative injury in uremic and aortic oxidative injury in atherosclerotic rats [9,23]. Paricalcitol has been shown to attenuate ciclosporin Ainduced nephropathy by suppression of inflammatory and apoptotic factors through inhibition of some protein kinase-signalling pathways [5]. De Zeeuw et al [24] demonstrated that paricalcitol lowers albuminuria in patients with diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its primary role in calcium metabolism and bone mineralisation, vitamin D and its non-hypercalcemic analogue paricalcitol have pleiotropic and antioxidant effects on cellular homeostasis [5]. Studies in experimental nephropathy models have focused on the effects of vitamin D and paricalcitol on glomerular damage and tubular toxicity [6][7][8].…”
mentioning
confidence: 99%
“…Beyond its role in calcium and phosphate homeostasis, vitamin D is an important modulator of cellular proliferation, inflammation, differentiation, and immunity [11]. Vitamin D3 attenuates kidney injury by suppressing fibrosis, inflammation, and apoptosis, by inhibiting multiple pathways known to play a role in kidney injury, including the renin-angiotensinaldosterone system (RAAS), the nuclear factor-κB (NF-κB) [11,12], the transforming growth factor-β (TGF-β)/Smad [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond its role in calcium and phosphate homeostasis, vitamin D is an important modulator of cellular proliferation, inflammation, differentiation, and immunity [14]. Vitamin D3 attenuates kidney injury by suppressing fibrosis, inflammation, and apoptosis, by inhibiting multiple pathways known to play a role in kidney injury, including the renin-angiotensinaldosterone system (RAAS), the nuclear factor-κB (NF-κB) [15], the transforming growth factor-β (TGF-β)/Smad [16].…”
Section: Citationmentioning
confidence: 99%